SINERGITAS COLLABORATIVE GOVERNANCE DALAM PENCEGAHAN DAN PENANGANAN PANDEMI COVID-19 KOTA SURABAYA - singgih manggalou (Halu Oleo University, 2022)
The purpose of this study was to determine the synergy between actors in the prevention and handling of Covid-19 in Surabaya. The super-fast transmission of the Covid-19 virus requires the Surabaya city government to take precautions in handling it. Prevention and handling is done by forming a task force according to the president's instructions. But unfortunately, the task force left the private sector, whereas in realizing good governance, three pillars are needed (government, private, and community) as key actors. This research method uses descriptive qualitative. Data collection techniques with in-depth interviews and literature study. The results of the study show that synergy and collaboration are carried out very well. This can be seen from the absence of institutional sectoral egos. Task force communication is carried out vertically and horizontally. Coordination with the community is also carried out regularly through the Kampung Tangguh